Non-neurotoxic activity of Malayan krait (Bungarus candidus) venom from Thailand - Charoenpitakchai, Mongkon (J Venom Anim Toxins Incl Trop Dis, 2018)
BACKGROUND: Envenoming by kraits (genus Bungarus) is a medically significant issue in South Asia and Southeast Asia. Malayan krait (Bungarus candidus) venom is known to contain highly potent neurotoxins. In recent years, there have been reports on the non-neurotoxic activities of krait venom that include myotoxicity and nephrotoxicity. However, research on such non-neurotoxicity activities of Malayan krait venom is extremely limited. Thus, the aim of the present study was to determine the myotoxic, cytotoxic and nephrotoxic activities of B. candidus venoms from northeastern (BC-NE) and southern (BC-S) Thailand in experimentally envenomed rats. METHODS: Rats were administered Malayan krait (BC-NE or BC-S) venom (50 μg/kg, i.m.) or 0.9% NaCl solution (50 μL, i.m.) into the right hind limb. The animals were sacrificed 3, 6 and 24 h after venom administration. The right gastrocnemius muscle and both kidneys were collected for histopathological analysis. Blood samples were also taken for determination of creatine kinase (CK) and lactate dehydrogenase (LDH) levels. The human embryonic kidney cell line (HEK-293) was used in a cell proliferation assay to determine cytotoxic activity. RESULTS: Administration of BC-NE or BC-S venom (50 μg/kg, i.m.) caused time-dependent myotoxicity, characterized by an elevation of CK and LDH levels. Histopathological examination of skeletal muscle displayed marked muscle necrosis and myofiber disintegration 24 h following venom administration. Both Malayan krait venoms also induced extensive renal tubular injury with glomerular and interstitial congestion in rats. BC-NE and BC-S venoms (100–0.2 μg/mL) caused concentration-dependent cytotoxicity on the HEK-293 cell line. However, BC-NE venom (IC(50) = 8 ± 1 μg/mL; at 24 h incubation; n = 4) was found to be significantly more cytotoxic than BC-S venom (IC(50) = 15 ± 2 μg/mL; at 24 h incubation; n = 4). In addition, the PLA(2) activity of BC-NE venom was significantly higher than that of BC-S venom. CONCLUSIONS: This study found that Malayan krait venoms from both populations possess myotoxic, cytotoxic and nephrotoxic activities. These findings may aid in clinical diagnosis and treatment of envenomed patients in the future.